2021
DOI: 10.21831/reid.v7i1.41644
|View full text |Cite
|
Sign up to set email alerts
|

English as a Foreign Language (EFL) learning assessment in single-sex and co-educational classrooms

Abstract: This study investigates the effects of Single-Sex and Co-educational classrooms on English learning outcomes. This study is a causal-comparative study in ex post facto design. Three classes consisting of 73 students (boy and girl-single-sex classes and a co-educational class) from a private secondary school in Central Java, Indonesia, are the sample. An integrated English test, equating the material from the 2013 curriculum and CEFR for English, was used. It tested four skills in English consisting of Listenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Some studies demonstrated positive effect of single-sex schooling on academic performance, including reading and writing (Dwarte, 2014;Farisiyah et al, 2021;Riordan, 2015;Rugutt & Chemosit, 2020;Sheymardanov, 2019)career, and life opportunities. Consequently, many urban school districts have implemented single-sex instructional programs in an effort to better address the schooling needs of African Americans.…”
Section: The Impact Of Gender Differences and Schooling On Writing At...mentioning
confidence: 99%
“…Some studies demonstrated positive effect of single-sex schooling on academic performance, including reading and writing (Dwarte, 2014;Farisiyah et al, 2021;Riordan, 2015;Rugutt & Chemosit, 2020;Sheymardanov, 2019)career, and life opportunities. Consequently, many urban school districts have implemented single-sex instructional programs in an effort to better address the schooling needs of African Americans.…”
Section: The Impact Of Gender Differences and Schooling On Writing At...mentioning
confidence: 99%